2019
DOI: 10.1177/0272684x19896730
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of School-Going Adolescents About the Oral Effects of Tobacco Usage in Ibadan, Southwest Nigeria

Abstract: Background The individual knowledge of the effects of tobacco usage on health plays an important role in its uptake. Tobacco consumption usually starts during adolescence, and lack of knowledge about the oral problems of tobacco usage probably plays a role in it. Aim To determine the knowledge of adolescents about the effect of tobacco usage on oral health. Methods A cross-sectional study was conducted among 1,465 adolescents aged 12 to 20 years who attended senior secondary schools in a major city in Nigeria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…High rates of low SK were observed, especially about the effects on oral health and the second-hand effects, indicating possibilities for improvements. These findings agree with several previous studies that observed low levels of knowledge on the harms of smoking among adolescents using objective measurements [5][6][7][8][9][10][11][12][13][14] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…High rates of low SK were observed, especially about the effects on oral health and the second-hand effects, indicating possibilities for improvements. These findings agree with several previous studies that observed low levels of knowledge on the harms of smoking among adolescents using objective measurements [5][6][7][8][9][10][11][12][13][14] .…”
Section: Discussionsupporting
confidence: 92%
“…Many adolescents may not be aware that smoking is harmful for their health [4][5][6][7][8][9] , especially regarding second-hand smoking [10][11][12][13] and oral health effects 14 . A lack of knowledge about the hazards of smoking has been described as a predictor of smoking status 13,[15][16][17][18] and susceptibility to smoking [19][20][21] in this population group.…”
Section: Introductionmentioning
confidence: 99%
“…The included articles studied a diverse Nigerian population groups totaling 7,883 people. Two articles surveyed smokers (age range: 15 -64 years) [51,55], 2 surveyed dental patients (age of majority: 18 -64 years) [46,49], one surveyed traditional healers and herbalists (age range: 37 -72 years) [43], 6 surveyed secondary school students (age of majority: <18 years) [53,54,56,61,63], 1 surveyed school teachers (mean (±SD) age: 48.7 (± 5.94) years) [45], 5 surveyed tertiary school students (age of majority: 15 -30 years) [48,52,58,59,60,62], 1 surveyed youth (age of majority (91%): 12 -24 years) [57], and 3 surveyed health workers (age: >18 years) [44,47,50] (Table 6).…”
Section: Characteristics Of the Studied Population Groupsmentioning
confidence: 99%
“…A higher proportion of the male smokers knew of this risk factor when compared with their female counterparts Kanmodi et al, 2017 [52] a) The age of the majority (92.4%) of the surveyed nursing students ranged from 15 to 35 years b) The majority (72.8%, n=115) of them were aware of OC; lectures (52.2%), books (43.5%), and newspapers (20.0%) were the top three sources of information regarding OC among them. Furthermore, hereditary factors (33.3%), cigarette smoking (26.2%), and mouth sore (26.2%) were the three most commonly known OC risk factors among this category of respondents c) The three most commonly known OC symptoms among those respondents that were aware of oral cancer (n=115) were ulcer/sore (86.1%), mouth swelling/lump (74.8%), and soft tissue discoloration (64.3%) Kanmodi & Fagbule, 2018 [53] a) The mean (±SD) age of the studied secondary school students was 13.89 (±1.01) years b) HNC education significantly improved the mean knowledge scores of the studied subjects on HNC etiology/risk factors and HNC symptoms c) HNC education significantly increased the number of the subjects who showed willingness to educate their peers about HNC d) 92.2% of the studied subjects enjoyed the HNC education session -the intervention offered to them Kanmodi et al, 2018 [54] a) The majority (95.9%) of the surveyed secondary school students were aged ≤18 years b) Only 47.5% of the respondents had heard of HNC before c) The majority (81.8%) of the respondents would like to receive a comprehensive education on how to prevent HNC in future Kanmodi et al, 2019 [55] a) The mean (±SD) age of the surveyed shisha smokers was 25.8 (±5.5) b) Only 17.8% of the surveyed respondents had heard of HNC c) The majority (73.3%) of the respondents would like to receive a comprehensive education on HNC Lawal & Fagbule, 2019 [56] a) The mean (±SD) age of the surveyed school-going adolescents was 15.2 (±1.4) years b) Only 0.1% (2/1465) of the survey respondents knew that tobacco can cause OC Kanmodi et al, 2019 [57] a) The majority (91%) of the surveyed youths were within the age range of 12 -24 years b) Only 49% of the survey respondents had ever heard of HNC c) Among those respondents that were aware of HNC, 66% of them knew that HNC is not a contagious disease; 69% believed that early diagnosis improves recovery from head and neck cancer; 24% believed that HNC is more common among people aged >40 years d) The majority (76%) of the survey respondents were positively disposed towards knowing more about HNC disease Kanmodi et al, 2019 [58] a) The mean (±SD) age of the surveyed monotechnic freshmen was 22.04 (±3.42) years b) Only 30.4% of the surveyed respondents were aware of HNC; human papillomavirus (36.8%), smoking (23.5%) and poor tooth brushing (23.5%) were the top three HNC etiological/risk factors known to this category of respondents (i.e. those that were aware of HNC).…”
Section: Knowledge Of Risk Factors and Clinical Features Of Hnc/ocmentioning
confidence: 99%
See 1 more Smart Citation